On the Variation of Intermittency of Fast and Slow Solar Wind With Radial Distance, Heliospheric Latitude, and Solar Cycle - Wawrzaszek, Anna; Echim, Marius (Frontiers in Astronomy and Space Sciences, 2021)
Intermittency, an important property of astrophysical plasma turbulence, is studied extensively during last decades from in-situ measurements of the solar wind plasma and magnetic field in the ecliptic plane and at higher latitudes, and heliocentric distances between 0.3 and 5 Astronomical Units. In this paper, we review the main findings on intermittency derived from investigation of solar wind turbulence for the inertial range of scales. It turns out that our current knowledge on the evolution of intermittency in the heliosphere is based on two missions, Helios 2 and Ulysses. We discuss the importance of data selection methodologies and applications for heliospheric spacecraft, the different data analysis techniques (the anomalous scaling of the structure function, the non-Gaussianity of the probability distribution functions, the local intermittency measure estimated from a wavelet representation and the multifractal spectrum). Studies show that Alvénic solar wind is less intermittent but reveals increase with the radial distance. Moreover, intermittency is stronger for the magnetic than for velocity fluctuations and is considered to be responsible for the increase with the radial distance of the anisotropy of magnetic fluctuations. The intermittency of fast solar wind at solar minimum decreases with latitude. Finally, the level of intermittency in the solar wind depends on solar cycle phase, reflecting the changes of the state of solar wind and suggesting that the deeper study of origin of fast and slow wind can further improve our understanding of the intermittency.